Transforming growth factor-β1 in the cerebrospinal fluid of patients with distinct neurodegenerative diseases. (January 2017) - Masuda, Tomoyuki; Itoh, Junko; Koide, Takuya; Tomidokoro, Yasushi; Takei, Yosuke; Ishii, Kazuhiro; Tamaoka, Akira
Highlights: We measured TGF-β1 in the CSF of patients with ALS, SCD, and MSA-C. We found that these TGF-β1 levels were not different from normal controls. TGF-β1 in the CSF is an unreliable biomarker of ALS, SCD, and MSA-C. Abstract: A chronic inflammatory condition may underlie neurodegenerative disorders, including Parkinson's disease (PD) and Alzheimer's disease (AD). For example, both PD and AD patients show an increase in transforming growth factor-β1 (TGF-β1) levels in their cerebrospinal fluid (CSF). TGF-β1 is a cytokine that inhibits inflammation. In the present study, using an enzyme-linked immunosorbent assay, we tested the hypothesis that the level of TGF-β1 in the CSF of patients with amyotrophic lateral sclerosis (ALS), spinocerebellar degeneration (SCD), or multiple system atrophy-cerebellar subtype (MSA-C) would be elevated compared with that of normal controls. We found that TGF-β1 levels in the CSF were not significantly different between these patients and normal controls. Our data suggest that the level of TGF-β1 in the CSF is an unreliable biomarker of ALS, SCD, and MSA-C.